2019
DOI: 10.5194/acp-19-3357-2019
|View full text |Cite
|
Sign up to set email alerts
|

Polyols and glucose particulate species as tracers of primary biogenic organic aerosols at 28 French sites

Abstract: A growing number of studies are using specific primary sugar species, such as sugar alcohols or primary saccharides, as marker compounds to characterize and apportion primary biogenic organic aerosols (PBOAs) in the atmosphere. To better understand their annual cycles, as well as their spatiotemporal abundance in terms of concentrations and sources, we conducted a large study focusing on three major atmospheric primary sugar compounds (i.e., arabitol, mannitol, and glucose) measured in various environmental co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
64
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 78 publications
10
64
1
Order By: Relevance
“…These values are comparable to those previ-11022 A. Samaké et al: Arabitol, mannitol, and glucose as tracers of primary biogenic organic aerosol ously reported for various sites in Europe (Daellenbach et al, 2017;Sánchez-Ochoa et al, 2007;Vlachou et al, 2018;Yttri et al, 2011b). Thus, a major part of PBOA could possibly be ascribed to cellulose and SC-derived sources.…”
Section: Influence Of the Vegetation On Polyol And Glucose Concentratsupporting
confidence: 83%
See 2 more Smart Citations
“…These values are comparable to those previ-11022 A. Samaké et al: Arabitol, mannitol, and glucose as tracers of primary biogenic organic aerosol ously reported for various sites in Europe (Daellenbach et al, 2017;Sánchez-Ochoa et al, 2007;Vlachou et al, 2018;Yttri et al, 2011b). Thus, a major part of PBOA could possibly be ascribed to cellulose and SC-derived sources.…”
Section: Influence Of the Vegetation On Polyol And Glucose Concentratsupporting
confidence: 83%
“…Therefore, only the "free cellulose" is reported in our samples. Note that Sánchez-Ochoa et al (2007) consider that this free cellulose could represent only about 70 % of the total cellulose in air samples and that the total cellulose could represent only about 50 % of the "plant debris" content of atmospheric PM. Very few other results are available on this topic (Bozzetti et al, 2016;Glasius et al, 2018;Vlachou et al, 2018;Yttri et al, 2011b).…”
Section: Chemical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The contrast between seasonal variation in particle number concentrations and that of EBC would suggest, as for the N 10-550 concentrations, that there are additional particle sources in the warm seasons originated from other processes than combustion. Samaké et al, (2019) [47], at 28 French sites (including the OPE site), showed higher concentrations of primary biogenic organic aerosols: polyols (sum of arabitol and mannitol) and glucose, which are mainly associated with the coarse mode, during the warmer seasons compared to colder seasons. Another source of these high concentrations in warm seasons could also be related to the abrasion of leaves and the subsequent release of microbial organisms and plant debris [48,49] and long-range transport of large particles from distant sources.…”
Section: Particle Number Concentrationsmentioning
confidence: 99%
“…The study of the origin of EBC (FF or BB), discussed before, also suggests a dominant contribution from anthropogenic activities, represented here by the FF combustion related to traffic. For particles in the size range 1.15-4.5 µm, there is a visible contribution of local sources of primary emissions due to local agricultural practices [47] and of marine aerosol. Samaké et al, (2019) [47] showed higher concentrations of primary biogenic organic aerosols, which are mainly associated with the coarse mode.…”
Section: Particle Number Concentrationsmentioning
confidence: 99%